Medicinal plants of Ecuador: a review of plants with anticancer potential and their chemical composition - Tinitana Imaicela, F. (2015)
Abstract: Ecuador is well known for its biodiversity and its ancient richness. This review provides an overview of Ecuadorian plant species in terms of the ethnobotany and chemistry of natural products in relation to anticancer activity. Plant species were classified into two groups: (a) Ethnomedical species with confirmed antitumor activity and (b) species indigenous to Ecuador with anticancer potential. This review shows that there is a great chemical diversity in Ecuadorian plants that can be used for potential antitumor therapeutics, and chemical and biological analysis confirms the biomedical use of the plant-derived compounds as cytotoxic agents for cancer cells.Graphical Abstract: [Figure not available: see fulltext.]